Harvesting energy of flow-induced vibrations using cylindrical piezoelectric transducers - Shehab Salem; Karel Fraňa (Energy Reports, 2023)
Piezoelectric transducers are used to harvest the energy of Flow-Induced Vibrations, FIVs. These transducers are mainly in the shape of a cantilever beam, although a cylindrical piezoelectric transducer has rarely been used. This work discusses the use of cylindrical piezoelectric transducers to harvest the energy of FIVs. Two cylinders made from Lead Zirconate Titanate, PZT, underwent closed-circuit wind-tunnel tests at wind speeds of 1 up to 7 m/s. The electric load was varied for each cylinder from 200 up to 800 kilo-Ohms. The cylinders had diameters of forty and ten millimetres and aspect ratios of one and three, respectively. It was possible to dissipate electric energy at a power of 370.6 pW across the load using the forty-millimetre-diameter cylinder at a flow speed of 1 m/s and a load resistance of 200 kΩ.